Analysis The Influence of Visitor Motivation on Visitor Satisfaction and Its Impact on Revisit Intention at Hype Pantai Indah Kapuk - Gio Sandro Aritonang (Social Economics and Ecology International Journal (SEEIJ), 2021)
The development of the times provides changes in consumer behavior in keeping with current trends. In Indonesia, thematic bazaar is a trend that is quite popular where it is indicated by the number of thematic bazaars that have sprung up today, one of which is Hype Pantai Indah Kapuk. The purpose of this study is to determine the effect of Visitor Motivation to Visitor Satisfaction and its impact on re-visit intention on Hype Pantai Indah Kapuk. The method of analysis of the study using anaylsis path with a sample of 100 respondents in Jakarta. The result of this research shows that there is influence of Visitor Motivation to Visitor Satisfaction at Hype Pantai Indah Kapuk, there is influence of Visitor Motivation towards Revisit Intention on Hype Pantai Indah Kapuk, there is no influence of Visitor Satisfaction toward Revisit Intention on Hype Pantai Indah Kapuk, and there is influence of Visitor Motivation and Visitor Satisfaction towards Revisit Intention on Hype Pantai Indah Kapuk.